PEMANFAATAN ARTIFICIAL INTELLIGENCE BERBASIS GOOGLE GEMINI DAN APPS SCRIPT DALAM TATA KELOLA SDM - Sholikin, Ahmad Nur; Nurkholivvah, Alivia; Hadini, Anggit Wahyu Nur; Roringkon, Christofel J. A.; Hidayaturahmi, Hidayaturahmi (Mediakom : Jurnal Ilmu Komunikasi, 2025)
This study is aimed to examine the implementation of an artificial intelligence (AI)-based recruitment system at the Human Resources Directorate of Universitas Indonesia, focusing on the selection of structural officers (section and subsection heads). Utilizing simple AI tools such as Google Gemini and Google Apps Script, the initiative aimed to enhance recruitment efficiency and objectivity. This study uses descriptive qualitative. The findings show that AI significantly improved the speed and accuracy of candidate screening, reduced administrative workload, and minimized unconscious bias thereby strengthening meritocracy. Furthermore, the role of HR professionals evolved from administrative functions to more analytical and strategic tasks. The success of this transformation is attributed to the application of a strong human-in-the-loop principle, ensuring that AI functions as a decision-support tool, with final decisions remaining under human authority. Challenges related to data format, algorithmic limitations, ethical concerns, and organizational resistance were effectively mitigated through standardized protocols, data protection policies, and change management strategies. The study also highlights key institutional innovations, including the formalization of standard operating procedures (SOPs), development of AI ethics guidelines, and a roadmap for wider AI adoption in HR functions. This case provides a replicable model for responsible and impactful use of AI in public sector HR management.